The role of developing breast cancer in alteration of serum lipid profile - Abdelsalam, Kamal Eldin A. (Medknow Publications & Media Pvt Ltd, 2012)
AIMS: The major aim of this study is to examine the role of alterations in lipid profile in women developing breast cancer. This study was carried out between May 2009 and December 2010. BACKGROUND: The relationship between lipids and breast cancer is undistinguished. Until now, conflicting results have been reported on the association between lipids and risk of breast cancer development in women. MATERIALS AND METHODS: Plasma lipids (i.e., total cholesterol [TC], high-density lipoprotein [HDL], low-density lipoprotein [LDL], and triglycerides [TG] were analyzed from 60 controls and 120 untreated breast cancer patients with clinical and histopathological evidence, under aseptic conditions. Venous blood was drawn from the cases and controls and estimations of lipid profile were done utilizing the standard procedures. STATISTICAL ANALYSIS USED: Independent sample t-test to compare the mean serum levels of lipid profile and TC/HDL ratio between patients and controls. RESULTS: A significant rise in serum total cholesterol, low-density lipoprotein cholesterol, and ratio of total cholesterol: high density lipoprotein cholesterol values, whereas high density lipoprotein cholesterol and very low density lipoprotein cholesterol were not affected significantly by the breast cancer. CONCLUSIONS: The developing breast cancer might be considered as one of the factors in alterations in lipid profile levels.